Associated factors of intestinal worm infection among Orang Asli school children in Tapah, Perak, Malaysia - Tunbsun, Olawumi Edward (2016)
Worm infection is one of the major global public health problems in human especially in the developing countries with about 135, 000 deaths annually. The highest prevalence of the infection is found among children between five to twelve years and usually those with deprived living resources. In Malaysia, despite a thriving economy, intestinal worm infection is very prevalent among the Orang asli population. The objective of the study was to determine the prevalence of intestinal worm infection and risk factors among the Orang Asli school children in Tapah, Malaysia. A crosssectional study was conducted among 411 Orang Asli school children aged 6-13 years in Tapah, Perak. Sample size was calculated using two proportion formula, and also selection of respondents using simple random sampling. Data was collected using questionnaires and laboratory fecal examination from the school children. The results showed that the overall prevalence of intestinal worm infection was 60.8% and about 57.2% presented with multiple infections. The predominant species was Trichuris trichura 53.8% among other nematodes. Few cestodes and trematodes were also recovered among the children. Intestinal worm infection was highest among age group 11-13 years (62.2%) and higher among males (65.5%). Multivariate analysis result showed that the predictors of intestinal worm infections among the Orang Asli children were presence of river (OR = 1.90; 95% CI = 1.16, 3.10; p = .011), presence of lake (OR = 0.21; 95% CI = 0.05, 0.93; p = .040), toilet system (OR = 1.67; 95% CI = 1.08, 2.56; p = .021), and general hygiene practice (OR = 2.15; 95% CI = 1.35, 3.41; p = .001). In conclusion, prevalence of intestinal worm infection is high. A deworming along with a comprehensive health education on intestinal worm infections program should be organized among this population group.